CONDOMÍNIOS EMPRESARIAIS EM ÁREAS METROPOLITANAS DO ESTADO DE SÃO PAULO: UMA NOVA ESTRATÉGIA IMOBILIÁRIA - Finatti, Rodolfo (GEOUSP Espaço e Tempo (Online), 2009)
The enterprises condominium are a kind of recent undertaking in Brazil and State of São Paulo. Generally speaking, they started in the end of the nineties decade and consists of new spaces for productive use. They express new manners of real estate capital, whose associates tendencies of productive, like the territorial flowing imperative, at urbanization and globalization in course. This work objective is to classify such undertakings, analyzing their main infra-structural characteristics and intentionality.